Biology of mistletoes and their status in Nepal Himalaya - Devkota, Mohan Prasad (Himalayan Journal of Sciences, 2007)
The mistletoes constitute a polyphyletic group of flowering parasitic plants and are commonly known as “Ainjeru” or “Lisso” in Nepali. Of the over 1300 mistletoe species occurring worldwide, Nepal is home to 19. Mistletoes are entirely dependent on their hosts for water and nutrients and affect their hosts mainly by competing for limited resources. Mistletoes play a vital role in natural plant communities by interacting with hosts, herbivores and dispersers. A large number of invertebrates and vertebrates use mistletoes as a shelter, as nesting and roosting place and as an important source of food. Oddly, botanists have accorded little attention to Nepal’s mistletoes, and our knowledge of this remarkable group of plants is quite deficient.Himalayan Journal of Sciences 3(5) 2005 p.84-86